PERLINDUNGAN KONSUMEN ATAS PEREDARAN PRODUK KOSMETIK POST MARKET MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN: Consumer Protection For The Distribution Of Post Market Cosmetic Products According To Law Number 8 Of 1999 Concerning Consumer Protection - Haya Alyssa Desti Ramadhani; Renti Maharaini Kerti (AMICUS CURIAE, 2025)
Consumer protection is an effort to ensure legal certainty in safeguarding consumer rights. This study examines the regulation of cosmetic product quality standards and the role of the National Agency of Drug and Food Control (BPOM) in conducting post-market surveillance to ensure compliance with established standards. The identified issues in this research are how the quality standards are applied to Scarlett Whitening body lotion products and how BPOM plays a role in ensuring the safety of these cosmetic products for consumers. This research uses a normative-descriptive method through literature study and interviews with consumers and BPOM officials. Based on the research findings and conclusions, it is concluded that every cosmetic product must comply with the established quality standards, and BPOM plays a crucial role in conducting both pre-market and post-market supervision. Although Scarlett Whitening products have fulfilled legal requirements in accordance with regulatory provisions, consumers have expressed dissatisfaction regarding the product’s heavy texture, difficulty of absorption, and lack of promised brightening effects. This highlights the importance of quality supervision not only in terms of legal compliance but also in ensuring consumer experience and satisfaction.